Development of White Bread Made from Sorghum Flour, Cassava, Arrowroot, and Red Spinach Extract as a High-Fiber Functional Food - Muhammad Vickry Fadly; Firman Muhammad Basar; Ksatriadi Widya Dwinugraha (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Dietary fiber is essential for digestive health, yet conventional wheat-based white bread is low in fiber and unsuitable for gluten-intolerant individuals. This study developed a high-fiber, gluten-free white bread using sorghum, cassava, and arrowroot flours combined with red spinach extract, with psyllium husk added to replicate gluten's viscoelastic properties and improve dough structure and texture. Using a Completely Randomized Design, three formulations were tested—F1 (sorghum 75 g : cassava 25 g : arrowroot 25 g), F2 (sorghum 50 g : cassava 50 g : arrowroot 25 g), and F3 (sorghum 25 g : cassava 75 g : arrowroot 25 g)—each with 80 ml red spinach extract and psyllium husk. Organoleptic testing (Kruskal-Wallis and Mann-Whitney) revealed significant differences in appearance, texture, and taste, while color and aroma were not significantly different. Formulation F2 was most preferred, containing per 100 g: 198 kcal, 3.7 g protein, 3.0 g fat, 38.8 g carbohydrates, and 7.77 g fiber. This gluten-free, high-fiber bread presents a promising healthier alternative that supports local food diversification and meets the needs of gluten-sensitive consumers.